Tuning Electronic Structure of NiFe Layered Double Hydroxides with Vanadium Doping toward High Efficient Electrocatalytic Water Oxidation. Issue 15 (12th February 2018) - Li, Pengsong; Duan, Xinxuan; Kuang, Yun; Li, Yaping; Zhang, Guoxin; Liu, Wen; Sun, Xiaoming
Abstract: Binary NiFe layer double hydroxide (LDH) serves as a benchmark non‐noble metal electrocatalyst for the oxygen evolution reaction, however, it still needs a relatively high overpotential to achieve the threshold current density. Herein the catalyst's electronic structure is tuned by doping vanadium ions into the NiFe LDHs laminate forming ternary NiFeV LDHs to reduce the onset potential, achieving unprecedentedly efficient electrocatalysis for water oxidation. Only 1.42 V (vs reversible hydrogen electrode (RHE), ≈195 mV overpotential) is required to achieve catalytic current density of 20 mA cm −2 with a small Tafel slope of 42 mV dec −1 in 1m KOH solution, which manifests the best of NiFe‐based catalysts reported till now. Electrochemical analysis and density functional theory +U simulation indicate that the high catalytic activity of NiFeV LDHs mainly attributes to the vanadium doping which can modify the electronic structure and narrow the bandgap thereby bring enhanced conductivity, facile electron transfer, and abundant active sites. Abstract : The vanadium doping in the laminate of nickel iron layered structure plays an important role in boosting oxygen evolution reaction performance, which affects the electronic structure and improves electric conductivity, favoring fast electron transfer. The nickel iron vanadium layer double hydroxides hold a low onset potential and high electrochemical durability, exhibiting unprecedentedly efficient electrocatalysis for water oxidation.